English Reading E-Module Based on Gamification and Contextual Teaching and Learning to Promote Reading Comprehension Skills - Utami, Isnaini Apri; Sunardi; Drajati, Nur Arifah (Journal of Education Technology, 2024)
Reading is one of the most taught skills in English lessons, but it is also the most complex skill to improve. The reading activities carried out by students only use textbooks and student worksheets, so they are less exciting and impact students' poor reading skills. This research aims to develop an electronic English reading module based on gamification and contextual learning that is appropriate to the needs of second language learners. This type of research is development research. This research is the second stage of Design-Based Research (DBR), which is the design and construction stage. The research subjects consisted of 2 learning materials experts, two ELT experts, and 2 English teachers. The test subjects were 35 tenth-grade students. This research uses quantitative descriptive analysis techniques and inferential statistics. Based on the results of data analysis, namely the assessment from learning material experts, 93% and 94% were obtained. The assessment from e-module content experts was 97% and 87%. The assessments given by the teacher were 81% and 90%. Usability testing from the student's perspective obtained 80%. From these results, an electronic English reading module based on gamification and contextual learning is suitable for use in the classroom. The implication of this research is that the gamification-based English reading electronic module that was developed can be used in learning.